Emotions, technology, design, and learning - Tettegah, Sharon Y.; Gartmeier, Martin 1976- (Academic Press, 2016)
Emotions, Technology, Design, and Learning provides an update to the topic of emotional responses and how technology can alter what is being learned and how the content is learned. The design of that technology is inherently linked to those emotional responses. This text addresses emotional design and pedagogical agents, and the emotions they generate. Topics include design features such as emoticons, speech recognition, virtual avatars, robotics, and adaptive computer technologies, all as relating to the emotional responses from virtual learning
Keywords: Educational innovations; Educational technology; Human-computer interaction; Gefühl; Embodiment; Mensch-Maschine-Kommunikation; Aufsatzsammlung